Geschichte der Venezianischen Malerei, Band 4 Tizian und sein Umkreis - Brucher, Günter (2015)
About a third of the present book deals with titian's artistic entourage: Paris Bordone, Palma Vecchio and Bonifazio de'Pitati. And, on the other hand, artists as Lorenzo Lotto, Pordenone, Savoldo, proving to be more self-contained, especially Pordenone.